Midbrain ghrelin receptor signalling regulates binge drinking in a sex specific manner - Amy J. Pearl; Xavier J. Maddern; Paulo Pinares-Garcia; Lauren T. Ursich; Roberta G. Anversa; Arnav Shesham; Robyn M. Brown; Felicia M. Reed; William J. Giardino; Andrew J. Lawrence; Leigh C. Walker (Nature Communications)
Abstract Risky drinking rates are rising, particularly in women, yet sex as a biological variable has only recently gained traction. The centrally projecting Edinger-Westphal (EWcp) nucleus has emerged as a key regulator of alcohol consumption. Here we found that EWcppeptidergic cells reduce binge drinking specifically in female mice. We show this effect is mediated by the ghrelin receptor (GHSR), with EWcppeptidergic inhibition blocking ghrelin-induced drinking and Ghsr knockdown in EWcppeptidergic, but not EWcpglutamatergic or ventral tegmental area cells, reducing binge drinking in females, independent of circulating sex hormones. Female mice showed higher EWcp Ghsr expression, and EWcppeptidergic neurons were more sensitive to ghrelin. Moreover, intra-EWcp delivery of GHSR inverse agonist and antagonist reduced binge drinking, suggesting direct actions of ghrelin. These findings highlight the EWcp as a critical mediator of excessive alcohol consumption via GHSR in female mice, offering insights into the ghrelin system’s role in alcohol consumption.